2020
DOI: 10.1177/0266242620918823
|View full text |Cite
|
Sign up to set email alerts
|

How do foreign entrepreneurs adapt to local corruption norms in the Middle East? Institutional multiplicities and individual adaptation

Abstract: Foreign entrepreneurs encounter institutional complexities resulting from differences between their home and host countries. On one hand, foreign entrepreneurs must adapt to local norms in a host environment that might be novel and different; on the other, foreign entrepreneurs bring institutional legacies from their home environments. In this article, we critically examine how such tensions affect norm adaptation by foreign entrepreneurs, focusing upon their attitudes towards corruption–defined as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…On the other hand, Fung a cov a et al (2015) found that SMEs often participate in corruption to bridge institutional voids. However, Liu et al (2020) found an inverse U shaped relationship between corruption propensity and SME performance. Our hypotheses are: JSMA 16,1 H1.…”
Section: Formal Institution and Smes' Performancementioning
confidence: 90%
“…On the other hand, Fung a cov a et al (2015) found that SMEs often participate in corruption to bridge institutional voids. However, Liu et al (2020) found an inverse U shaped relationship between corruption propensity and SME performance. Our hypotheses are: JSMA 16,1 H1.…”
Section: Formal Institution and Smes' Performancementioning
confidence: 90%
“…Entrepreneurs in the Middle East may be local or foreign. Local entrepreneurs are those born and raised in the country in which they are now operating, whereas foreign entrepreneurs have travelled from their home countries to reside and seek entrepreneurial opportunities in the host country (Kulchina, 2016(Kulchina, , 2017Liu et al, 2020). These two groups of entrepreneurs differ in several respects.…”
Section: System Justification and Entrepreneurs' Attitudinal Change Toward Corruptionmentioning
confidence: 99%
“…The opposing camp views corruption as a corrosive disruption that destroys trust, distorts resource allocation and stifles economic growth (Boudreaux et al, 2018; Budak and Rajh, 2014; Dutta and Sobel, 2016; Zyglidopoulos et al, 2017). In either case, corruption is pervasive in many societies, particularly in emerging economies where institutional voids are common (Cuervo-Cazurra, 2006; Rodriguez et al, 2005; Liu et al, 2020; Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%